ANALYSIS OF THE STUDENTS' AWARENESS LEVEL AT MTs AL-ITTIHADIYAH MEDAN REGARDING THE IMPORTANCE OF LEARNING ARABIC IN THE EDUCATIONAL ENVIRONMENT - Alawiyah, Sofy; al Rasyid, Harun (Abjadia : International Journal of Education, 2024)
This paper explains the analysis of the awareness level of ninth-grade students at MTs al-Ittihadiyah Medan regarding the importance of learning Arabic in the educational environment. The research method used is descriptive qualitative, with data collection techniques through direct observation and semi-structured interviews with ninth-grade students of MTs Al-Ittihadiyah Medan. The findings of this research are as follows. First, ninth-grade students are not interested in participating in Arabic language learning at school. Second, ninth-grade students at MTs Al-Ittihadiyah are less aware of the importance of Arabic language learning at school. By analyzing the awareness level of ninth-grade students at MTs al-Ittihadiyah Medan regarding the importance of learning Arabic, it will help teachers in building students' interest in learning Arabic not only from the aspect of material presentation or teaching methods but also by instilling awareness in students at the beginning of the lesson about the purpose and importance of learning Arabic in school.